2007
DOI: 10.1002/cncr.23157
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to recruiting underrepresented populations to cancer clinical trials: A systematic review

Abstract: they examined reference lists for eligible articles. Titles and abstracts were reviewed to identify relevant studies. Data on barriers to participation were synthesized both qualitatively and based on statistically significant associations with trial enrollment. Of 5257 studies that were cited, 65 studies were eligible for inclusion in the current analysis, including 46 studies on recruitment into cancer therapeutic trials, 15 studies on recruitment into prevention trials, and 4 studies on recruitment into bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
894
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 921 publications
(927 citation statements)
references
References 119 publications
28
894
4
1
Order By: Relevance
“…Diverse medically underserved communities are less aware of opportunities to participate in biospecimen donation for cancer research as shown in our study and by others that have focused on recruiting underrepresented populations to cancer clinical trials (Ford et al 2008); however, this lack of awareness did not translate to a lack of interest in participating in the research. As shown in similar studies, the use of a community-based education/outreach program facilitated engagement of diverse community participants and provided them with information on a novel opportunity to participate in cancer research through biospecimen donation (Dash et al 2014;Gao et al 2014;Hagiwara et al 2014).…”
Section: Discussionmentioning
confidence: 56%
“…Diverse medically underserved communities are less aware of opportunities to participate in biospecimen donation for cancer research as shown in our study and by others that have focused on recruiting underrepresented populations to cancer clinical trials (Ford et al 2008); however, this lack of awareness did not translate to a lack of interest in participating in the research. As shown in similar studies, the use of a community-based education/outreach program facilitated engagement of diverse community participants and provided them with information on a novel opportunity to participate in cancer research through biospecimen donation (Dash et al 2014;Gao et al 2014;Hagiwara et al 2014).…”
Section: Discussionmentioning
confidence: 56%
“…2,7 Research and interventions have sought to address patient and community factors that impede the recruitment of diverse study participants; it is also important to address clinic-based and provider factors that impede accrual to clinical trials.…”
mentioning
confidence: 99%
“…Cultural and languagebarriers have often been implicated as reason for low recruitment and poor retention of cancer participants (Ford et al, 2008;Gul and Ali, 2010;Symonds et al, 2012 our Qigong trial, language was not the major barrier but cultural issues may well be a key contributor to the attrition rate as we observed a pattern in the different ethnic groups. A recent study by Hui and colleagues (2012) showed that high cancer patients attrition were associated with various patient characteristics and a high baseline symptom burden such as dyspnea (OR, 1.06; p=0.01), fatigue (OR, 1.08; p=0.01), Hispanic race (OR, 1.87; p=0.002), higher level of education (p=0.02), longer study duration (p=0.01), and outpatient studies (p=0.05).…”
Section: Discussionmentioning
confidence: 60%
“…Participants' adherence to behavioral interventions like Qigong trial is often challenging, particularly in trials of complex interventions, or interventions which involve multiple visits (Courneya et al, 2005), require behavioral changes (Oh et al, 2010), or the involvement of engagement of multilingual, multicultural groups with varying educational level (Ford et al, 2008;Loh, 2009). Therefore, 'multiple difficulties in recruitment, retention of trials patients, and recruitment of cancer patients to trials have been reported (Melinda et al, 2008).…”
Section: Barriers To Participation In a Randomizedmentioning
confidence: 99%
See 1 more Smart Citation